High Genetic Variability of Norovirus Leads to Diagnostic Test Challenges. (4th October 2017) - Pang, Xiaoli; Zhuo, Ran; Qiu, Yuanyuan; Parsons, Brendon; Lee, Bonita; Chui, Linda; Freedman, Stephen
Abstract: Background: It is important to understand the diagnostic accuracy of syndromic multiplex panels such as the Luminex xTAG ® Gastrointestinal Pathogen Panel (GPP) as they are increasingly employed as routine diagnostic tests in laboratories worldwide. Recent evaluations in our laboratory identified lower detection rates of norovirus genogroup II (NoV GII) using the GPP as compared with our lab-developed RT-qPCR Gastroenteritis Virus Panel (GVP). This study is to characterize the NoV strains in samples with discordant NoV GII test results between GPP and GVP and determine the sensitivity of the two assays for specific NoV GII genotypes. Methods: We genotyped all NoV GII strains with discordant test result in stool samples or rectal swabs collected prospectively from a cohort of children with acute gastroenteritis between December 2014 and July 2016. The sensitivity of GVP and GPP for NoV GII were compared by analyzing GVP threshold cycle (Ct) and using ten-fold serial dilutions of positive samples of various NoV GII genotypes. Results: All discordant samples (11%; 63/607) tested positive for NoV GII by GVP but negative by GPP. Thirty-five percent (22/63) were successfully genotyped; 64% (14/22) of those were NoV GII genotype 2 (GII.2). The median Ct value of concordant positive was lower than those with discordant results (19.8 vs.. 33.7 respectively; P < 0.0001). GVP was 10-fold and at least 10, 000-fold more sensitive than GPP in detecting NoV GII.3 and GII.2, respectively, but has similar sensitivity for NoV GII.4. The GII.2 variants with discordant test results differed genetically from the concordant GII.2 variants. Conclusion: GPP has suboptimal sensitivity to detect NoV GII.2 and its use may lead to an underestimation of NoV disease burden with some cases not being detected. Disclosures: All authors: No reported disclosures.